3D analysis of anchor bolt pullout in concrete materials using the non-ordinary state-based peridynamics. (15th February 2019) - Lu, Jiezhi; Zhang, Yaoting; Muhammad, Habib; Chen, Zhijun; Xiao, Yunfeng; Ye, Binbin
Highlights: Development of a numerical method for the modeling of 3D anchor pull-out from concrete block. The Drucker–Prager plasticity model is implemented to describe the nonlinear of concrete material. The Hughes and Winget algorithm is integrated in NSPD for large deformation analysis. The pullout capacity and final failure mode of the anchor obtained are agreed well with the current design formula and the experimental observations. Abstract: In this work, a meshless analysis based the non-ordinary stated-based peridynamic method (NSPD) is performed to solve the problem of anchor bolt pullout in plain concrete. The peridynamic method is adopted as an analysis tool to avoid the difficulties found in FEM. In the analysis, the Drucker–Prager plasticity model is implemented to describe the nonlinear relationship between force vector state and deformation vector state. The Hughes and Winget algorithm is integrated in NSPD for large deformation analysis. The whole progressive failure process of the 3D anchor system, consisted of five groups with different embedment depth or member thickness, are investigated. Numerical analysis results indicate that the obtained peak pullout load shows good agreement with the current design formula and the crack branching of anchoring system also agreed well with the experimental investigations.